The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.2500/ajra.2016.30.4348
|View full text |Cite
|
Sign up to set email alerts
|

The Triple Aim and its Implications on the Management of Chronic Rhinosinusitis

Abstract: With the advent of ACOs, a paradigm shift in the treatment of CRS is inevitable to better conform to the goals of the Triple Aim. Future treatment algorithms will need to account for the heterogeneity within CRS and seek to identify appropriate timing and interventions for patients on an individual basis if the value of health care is to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In other words, there may have been less improvement in health‐related QOL after ESS with increasing surgical wait time. This finding supports the observations from Hopkins et al., as delaying surgery in refractory CRS may lower prognosis due to alteration of the sinonasal architecture …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In other words, there may have been less improvement in health‐related QOL after ESS with increasing surgical wait time. This finding supports the observations from Hopkins et al., as delaying surgery in refractory CRS may lower prognosis due to alteration of the sinonasal architecture …”
Section: Discussionsupporting
confidence: 92%
“…To carry out this endeavor, 6 parameters are to be addressed: safety, effectiveness, patient centeredness, efficiency, equity, and timeliness . Within the context of medically recalcitrant chronic rhinosinusitis (CRS), there is evidence to suggest that timeliness of surgery represents an opportunity to improve care, because early surgical intervention may prevent the progression of CRS pathophysiology and the development of comorbid conditions, thereby reducing healthcare utilization . Benninger et al .…”
mentioning
confidence: 99%
“…5 Furthermore, healthcare institutions are encouraged to work towards the triple aim put forth by the Institute for Healthcare Improvement for improved population health, improved patient experience of care, and lowered costs, which places further emphasis on the quality of care delivered. 6 …”
mentioning
confidence: 99%
“…With otolaryngology having been slow to transition to this new payment model, it is imperative that we stay engaged and take a proactive role in this process because it has great implications on our patients' outcomes and our own practices. Several articles in this issue of American Journal of Rhinology & Allergy contain themes relevant to this type of change.First is an intriguing article by Barry et al,1 who examined what the contemporary literature shows about early versus aggressive management of chronic rhinosinusitis (CRS) as it relates to patient experience, health outcomes, and overall cost burden. Their review demonstrated that early intervention with endoscopic sinus surgery in appropriately selected patients has the potential to improve outcomes and reduce the long-term cost burden of CRS.…”
mentioning
confidence: 99%
“…First is an intriguing article by Barry et al, 1 who examined what the contemporary literature shows about early versus aggressive management of chronic rhinosinusitis (CRS) as it relates to patient experience, health outcomes, and overall cost burden. Their review demonstrated that early intervention with endoscopic sinus surgery in appropriately selected patients has the potential to improve outcomes and reduce the long-term cost burden of CRS.…”
mentioning
confidence: 99%